Clinical and Microbiological Characterization of Osteoarticular Infections in Children from a clinic in Rionegro, Antioquia - Hoyos Orrego, Alvaro; Echeverri Ramirez, Natalia; Moreno Ramírez, Santiago; Herrera Vargas, Jhojan (Iatreia)
Introduction: Osteomyelitis and septic arthritis are common invasive bacterial infections in children. Objective: To describe the microorganisms, antimicrobial susceptibility, and microbiological diagnostic procedures. Methods: A case series of children with a confirmed diagnosis from 2017 to 2022 was characterized. Results: Forty-eight out of 84 patients were included in the study. The diagnoses were osteomyelitis in 20.8%, septic arthritis in 37.5%, and osteoarthritis in 41.6% of cases. Isolated microorganisms included methicillin-susceptible Staphylococcus aureus (MSSA) in 30.7% of cases, methicillin-resistant S. aureus (MRSA) in 28.8%, Pseudomonas aeruginosa in 5.7%, S. epidermidis in 3.8%, Escherichia coli in 3.8%, Enterococcus faecalis in 3.8%, Aeromonas hydrophila in 3.8%, Mycobacterium tuberculosis in 1.9%, and Salmonella spp. in 1.9%, among others. In 40 infections originating from skin and soft tissues, orthopedic hardware, limb trauma, and without an identified source, MSSA/MRSA predominated (75%). MSSA/MRSA showed susceptibility to vancomycin at 100%, trimethoprim-sulfamethoxazole at 100% and 93%, and clindamycin at 100% and 86.6%, respectively. Blood cultures (n = 22), synovial tissue cultures (n = 7), bone cultures (n = 28), and bone pus or synovial fluid in blood culture bottles (n = 3) were 100% positive. Conclusions: S. aureus was the most frequent microorganism with a high proportion of MRSA. MRSA exhibited high susceptibility to trimethoprim-sulfamethoxazole and vancomycin. The high positivity of primary cultures suggests the importance of always obtaining them.